(untitled) (Vietnam Journal of Community Medicine, 2023)
Introduction: Peptic ulcer disease is a prevalent and frequently recurring ailment, characterized by evolving etiological factors and risk elements that present difficulties in its management. Consequently, the quality of life of those suffering from peptic ulcers might be substantially influenced, thereby raising concerns. Objective: To develop a Vietnamese version of the Quality-of-Life Instruments for Chronic Diseases - Peptic Ulcer Scale (QLICD-PU), a specialized tool designed to assess the QLICD-PU’ patients. Materials and methods: In the month of April 2023, a cross-sectional study was undertaken. The data were obtained by conducting direct interviews with patients diagnosed with peptic ulcer disease (PUD) who were undergoing therapy. The interviews were conducted using the QLICD-PU tool. Results: The study involved a sample size of 146 patients. The examination of the reliability scale resulted in Cronbach’s alpha coefficient that above 0.6. The findings of the Exploratory Factor Analysis (EFA) indicated that all items demonstrated factor loadings of at least 0.3. In the context of Confirmatory Factor Analysis (CFA), the majority of the scale’s components demonstrated satisfactory model fit indices, with the exception of the GFI and NFI indices pertaining to the general Quality of Life (QoL) and PUD-specific sections. Conclusion: The validity and reliability of the Vietnamese adaptation of the QLICD-PU Quality of Life measure have been demonstrated, rendering it a valuable instrument for evaluating the QLICDPU in Vietnam.